Un/Convention(al) Refugees: Contextualizing the Accounts of Refugees Facing Homophobic or Transphobic Persecution - Jordan, Sharalyn R. (Refuge: Canada’s Journal on Refugees, 2011)
Propelled by fear of violence and flight from stigma, impelled by desire for connection and belonging, the movements of people whose sexualities or genders defy and offend norms cover a complex spatial, social, and psychological terrain. This paper presents partial findings of a critical qualitative inquiry conducted in partnership with Rainbow Refugee Committee, a community organization that supports and advocates with Queer, Lesbian, Gay, Bisexual, Trans (LGBTQ) and HIV-positive refugee claimants/ migrants. This inquiry into how queer refugees engage in settlement comprised participation in Rainbow Refugee Committee and narrative interviews with LGBTQ refugee claimants and refugees, as well as interviews with service providers, community organizers, and lawyers. This paper explores how pre-settlement experiences conditioned possibilities for safety and belonging through refugee protection. While seeking refugee protection, queer refugees are evaluated against expected narratives of refugee flight and of LGBT identity. This paper reflects on the unconventionality of queer refugees’ accounts in relation to these expectations. Queer refugees settling in Canada recounted surviving persecution by dis/avowing their desires, distancing/ taking on available identities, avoiding/seeking out others, and conforming/escaping. They pursued mixed, often precarious, migration trajectories constrained by tightening migration controls and the relative obscurity of refugee protection for sexual or gender-based persecution. In their hearings, they struggled with and against Western cultural narratives of sexual and gender identities, coming out, and gender dysphoria. Interview excerpts highlight relational agencies in claimants’ engagements with the refugee system.